2015
DOI: 10.1177/0143624415603004
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance of a typical residential Cyprus building with phase change materials

Abstract: This work investigates the thermal performance of a typical building in Cyprus, and the effect of application of a particular passive technology (phase change material or PCM) with the aim of reducing indoor air temperatures and energy supplied for the cooling season. Phase change materials for passive building applications are an emerging technology and have not been tested for the buildings of Cyprus, either by computer simulation or practical application. In this paper, the effect of incorporating a phase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
1
11
0
3
Order By: Relevance
“…Similar results were found in Portugal where a study has demonstrated that using PCM could enhance the thermal inertia of the house and so reduce the amplitude of the indoor temperature variation and increase the comfort level [16]. In Cyprus, the addition of a 0.15 m thick layer of PCM helped decrease the summer mean indoor temperature of 1.7˝C [17]. For Seong et al [18] different kinds of PCMs were especially added to lightweight buildings and used with night ventilation to decrease the indoor air temperature of up to 0.85˝C during the summer time.…”
Section: Introductionsupporting
confidence: 73%
“…Similar results were found in Portugal where a study has demonstrated that using PCM could enhance the thermal inertia of the house and so reduce the amplitude of the indoor temperature variation and increase the comfort level [16]. In Cyprus, the addition of a 0.15 m thick layer of PCM helped decrease the summer mean indoor temperature of 1.7˝C [17]. For Seong et al [18] different kinds of PCMs were especially added to lightweight buildings and used with night ventilation to decrease the indoor air temperature of up to 0.85˝C during the summer time.…”
Section: Introductionsupporting
confidence: 73%
“…Phase change materials have been successfully used for reducing the cooling load of office buildings utilizing naturally or fan-assisted night ventilation [92][93][94]. Studies in night ventilation have been carried out in different climate zones worldwide with different applications of PCMs.…”
Section: Night Ventilation and Phase Change Materialsmentioning
confidence: 99%
“…Also, some authors have investigated the effect of fan-assisted night ventilation with high ratios of air exchange per hour (ach) which was highly effective to discharge the PCM. Studies have found that the integration of natural night ventilation strategies [69,82] or fan-assisted night ventilation [103] can effectively increase the cooling performance of the PCM-enhanced buildings in climates with cool nighttime outdoor temperature. For example the effectiveness of night ventilation to enhance the performance of PCM passive system was investigated by Evola et al [70].…”
Section: Passive Pcm-enhanced Building With Natural Ventilationmentioning
confidence: 99%